Integrity of Financial Statements: An Empirical Study in Indonesia - Suzan, Leny; Iqbal, Muhammad (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
The integrity of financial reporting depends on the accuracy and objectivity of the data given. Another technique to assess a company's reliability in providing financial data is by looking at their reporting integrity. The purpose of  this  study  is  to  investigate  the  relationship  between  intellectual  capital,  leverage,  and  the  credibility  of financial  statements  from  an  institutional  ownership  perspective.  The  following  transportation  and  logistics businesses  were  chosen  using  a  purposive  sample  technique:  all  companies  listed  on  the  Indonesia  Stock Exchange from 2018 to 2022. The researchmethodology for this study is panel data regression, and Eviews 12 will be used for data analysis. The study's findings indicate that all three independent factors have an impact on financial report integrity concurrently; Intellectual capital has no effect, Leverage has a negative impact, and institutional ownership positive effect.